A Critical Review of Zebrafish Models of Parkinson’s Disease - Doyle, Jillian M.; Croll, Roger P. (Frontiers in Pharmacology, 2022)
A wide variety of human diseases have been modelled in zebrafish, including various types of cancer, cardiovascular diseases and neurodegenerative diseases like Alzheimer’s and Parkinson’s. Recent reviews have summarized the currently available zebrafish models of Parkinson’s Disease, which include gene-based, chemically induced and chemogenetic ablation models. The present review updates the literature, critically evaluates each of the available models of Parkinson’s Disease in zebrafish and compares them with similar models in invertebrates and mammals to determine their advantages and disadvantages. We examine gene-based models, including ones linked to Early-Onset Parkinson’s Disease: PARKIN, PINK1, DJ-1, and SNCA; but we also examine LRRK2, which is linked to Late-Onset Parkinson’s Disease. We evaluate chemically induced models like MPTP, 6-OHDA, rotenone and paraquat, as well as chemogenetic ablation models like metronidazole-nitroreductase. The article also reviews the unique advantages of zebrafish, including the abundance of behavioural assays available to researchers and the efficiency of high-throughput screens. This offers a rare opportunity for assessing the potential therapeutic efficacy of pharmacological interventions. Zebrafish also are very amenable to genetic manipulation using a wide variety of techniques, which can be combined with an array of advanced microscopic imaging methods to enable in vivo visualization of cells and tissue. Taken together, these factors place zebrafish on the forefront of research as a versatile model for investigating disease states. The end goal of this review is to determine the benefits of using zebrafish in comparison to utilising other animals and to consider the limitations of zebrafish for investigating human disease.